Age-related impact of depressive symptoms on functional capacity measured with 6-minute walking test in coronary artery disease. (May 2014) - Baldasseroni, Samuele; Pratesi, Alessandra; Orso, Francesco; Foschini, Alice; Marella, Andrea Giosafat; Bartoli, Nadia; Mossello, Enrico; Bari, Mauro Di; Marchionni, Niccolò; Tarantini, Francesca
Background: Patients affected by coronary artery disease (CAD) have a high prevalence of depressive disorders. It has been suggested that depressive symptoms significantly reduce exercise stress test performance in CAD patients, whereas their influence on functional capacity tests, such as the 6-minute walking test (6WT), has been less investigated. The aim of this study was to evaluate the correlation between depressive symptoms and 6WT in patients with CAD and the role of age on this relationship. Methods: We enrolled 148 CAD patients. Global functional capacity was measured with 6WT and the presence of depressive symptoms with the 30-item Geriatric Depression Scale (GDS). GDS score was analysed as a continuous variable or categorized as depression absent (score <10), probable (10–14), or present (≤15). Results: A significant inverse correlation was observed between GDS score and distance walked at 6WT. Patients positive for depressive symptoms (probable or present) had a significantly worse performance compared to those with GDS score <10. In multivariable analysis adjusted for indexes of cardiovascular disease severity and comorbidity, the presence of depressive symptoms proved to be an independent predictor of distance walked at 6WT; the predictivity of depressive symptoms on 6WT was age dependent. Conclusions: Depressive symptoms negatively affect 6WT performance among older CAD subjects. Non-cardiovascular parameters, such as psycho-affective disorders, must be taken into account for the interpretation of 6WT performance in old age.